Heparin modulates the endopeptidase activity of Leishmania mexicana cysteine protease cathepsin L-Like rCPB2.8. - Wagner A S Judice; Marcella A Manfredi; Gerson P Souza; Thiago M Sansevero; Paulo C Almeida; Cláudio S Shida; Tarsis F Gesteira; Luiz Juliano; Gareth D Westrop; Sanya J Sanderson; Graham H Coombs; Ivarne L S Tersariol (PLoS ONE)
Background Cysteine protease B is considered crucial for the survival and infectivity of the Leishmania in its human host. Several microorganism pathogens bind to the heparin-like glycosaminoglycans chains of proteoglycans at host-cell surface to promote their attachment and internalization. Here, we have investigated the influence of heparin upon Leishmania mexicana cysteine protease rCPB2.8 activity. Methodology/principal findings THE DATA ANALYSIS REVEALED THAT THE PRESENCE OF HEPARIN AFFECTS ALL STEPS OF THE ENZYME REACTION: (i) it decreases 3.5-fold the k 1 and 4.0-fold the k -1, (ii) it affects the acyl-enzyme accumulation with pronounced decrease in k 2 (2.7-fold), and also decrease in k 3 (3.5-fold). The large values of ΔG  =  12 kJ/mol for the association and dissociation steps indicate substantial structural strains linked to the formation/dissociation of the ES complex in the presence of heparin, which underscore a conformational change that prevents the diffusion of substrate in the rCPB2.8 active site. Binding to heparin also significantly decreases the α-helix content of the rCPB2.8 and perturbs the intrinsic fluorescence emission of the enzyme. The data strongly suggest that heparin is altering the ionization of catalytic (Cys(25))-S(-)/(His(163))-Im(+) H ion pair of the rCPB2.8. Moreover, the interaction of heparin with the N-terminal pro-region of rCPB2.8 significantly decreased its inhibitory activity against the mature enzyme. Conclusions/significance Taken together, depending on their concentration, heparin-like glycosaminoglycans can either stimulate or antagonize the activity of cysteine protease B enzymes during parasite infection, suggesting that this glycoconjugate can anchor parasite cysteine protease at host cell surface.